Management of supply chains with attribute-sensitive products: a comprehensive literature review and future research agenda. Issue 4 (22nd September 2020) - Amini, Mehdi; Bienstock, Carol C.; Golias, Mihalis
Abstract : Purpose: Mismanagement of supply chain operations may lead to waste of products and incur substantial monetary losses. This is particularly true for products with attributes that hasten deterioration, e.g. time, temperature, humidity and barometric pressure. Attribute-sensitive products must be carefully monitored throughout all supply chain processes to ensure acceptable quality to the end customers. This paper presents a comprehensive review of the scientific literature on attribute sensitive products and on attribute sensitive supply chains. The collected studies were reviewed using the content analysis method, focusing on the following aspects of attribute sensitive products: (1) industries; (2) product categories; (3) decisions involved; (4) processes; (5) current issues; (6) sustainability concerns; (7) research methods used; (8) objectives of decision makers; (9) solution approaches used; (10) incentives driving management and (11) future research issues. Based on the analysis of findings, gaps are identified, and future research directions are proposed. Design/methodology/approach: Literature review and content analysis. Findings: The authors discovered that, while the importance of product attributes vary from one industry to the other, overall the time attribute was critical in all of the industries considered in this literature review. Coordination, customer satisfaction, reliability and safety were key issues in attribute sensitive product supply chains (asp-SCs). Similar to the typical supply chains, asp-SCs face economic, social and environmental sustainability issues. However, the majority of the studies in our analysis emphasized importance of the social sustainability. The majority of the papers were reviewed and analyzed and adopted the modeling approach as a research method. Furthermore, it was found that asp-SCs were mostly driven with customer demands and social pressure. Research limitations/implications: Based on the literature review and content analysis, there are a number of directions for the work conducted in this study to be extended in several directions. First, the literature search could be expanded by relaxing some of the restrictions (e.g. include the conference papers and articles from on-line business journals). Second, additional scientific publishers can be considered (e.g. Emerald Insight–www.emeraldinsight.com ; Inderscience–www.inderscience.com ). The latter two extensions would allow a more precise assessment of published to date work on asp-SC operations. Third, our findings could be validated based on interviews with professionals and executives from companies dealing with asp-SCs. Such validation will allow identification of the differences between the state of the art and the state of practice. Practical implications: Supply chains that handle attribute sensitive products (asps) must consider the complexity of products that significantly change their properties due to factors such as time, temperature, barometric pressure, humidity. Mismanagement of operations within such supply chains may lead to significant product waste, as well as substantial monetary losses. Originality/value: This study presented a comprehensive literature review and content analysis of studies dealing with asps in the following industries: fashion, food, healthcare, humanitarian and pharmaceutical industries